Manganese-modified biochar promotes Cd accumulation in Sedum alfredii in an intercropping system. (15th January 2023) - Chen, Xuejiao; Lin, Qimei; Xiao, Hongyang; Muhammad, Rizwan
Abstract: Intercropping of crops with hyperaccumulators is a sustainable method to remediate contaminated soil without impeding agro-production. However, the function of engineered biochar in intercropping systems and its possible influence on cadmium (Cd) accumulation in hyperaccumulators remain unknown. A root box experiment on celery and Sedum alfredii with and without root separation was conducted in this study. Pristine and KMnO4 -modified biochar (BCMn ) were used to investigate the effects of different biochars on plant growth and Cd uptake in an intercropping system, as well as the influence of engineered biochar on Cd accumulation in hyperaccumulators. The results demonstrated that soil pH did not significantly vary with biochar application in the root separation treatment. However, BCMn significantly increased soil pH and thus reduced available Cd when the plant roots were not separated. Intercropping (no separation treatment) led to a 34% higher and 24% lower aboveground biomass of celery and S. alfredii, respectively, regardless of biochar addition. Compared with aboveground plant parts, plant roots exhibited more significant responses to biochar. Interestingly, intercropping may favour the phytoextraction of Cd by S. alfredii . In particular, the Cd uptake by S. alfredii roots substantially increased (118–187%), whereas that of celery roots decreased (51–71%) with BCMn addition, compared with other treatments. Moreover, after BCMn addition the accumulation of Cd in aboveground S. alfredii in the no separation treatment was 136% higher than that in the separation treatment. This was possibly related to the interaction of manganese (Mn) with Cd as well as the roots of S. alfredii . These findings provide new insights into the application of engineered biochar for phytoextraction, which is important for the efficient remediation of Cd-contaminated soils. Graphical abstract: Image 1 Highlights: Mn-modified biochar (BCMn ) increased soil pH and decreased the available Cd content. The growth and architecture of plant roots were sensitive to biochar addition. Intercropping with celery may hinder the growth of S. alfredii. BCMn promoted the Cd accumulation in S. alfredii intercropped with celery.